The Role of Organizational Commitment as a Mediation on the Influence of Work-Life Balance on Organizational Citizenship Behavior - Astuti, Dwi; Daspar, Daspar (International Journal of Applied Finance and Business Studies, 2024)
This study investigates the mediating role of Organizational Commitment in the relationship between Work-Life Balance (WLB) and Organizational Citizenship Behavior (OCB) among employees in Indonesian manufacturing companies. As organizational competitiveness increasingly relies on proactive and voluntary employee behaviors, understanding how work-life balance influences such behaviors is vital. Employing a quantitative method and utilizing SmartPLS for structural equation modeling, data were collected from 68 respondents through a structured questionnaire. The results show that while WLB does not significantly impact OCB directly, it exerts a strong and significant influence on Organizational Commitment, which in turn significantly enhances OCB. Mediation analysis confirms that Organizational Commitment plays a crucial intervening role in translating work-life balance into discretionary behaviors. These findings suggest that creating a supportive work-life environment strengthens employee attachment to the organization, thereby encouraging behavior that goes beyond formal job responsibilities. This research contributes both theoretically and practically by highlighting the importance of integrated HR strategies that foster commitment to enhance citizenship behavior in industrial workplaces.